Probabilistic Relational Hoare Logics for Computer-Aided Security Proofs - Barthe, Gilles; Grégoire, Benjamin; Zanella-Béguelin, Santiago (11th International Conference on Mathematics of Program Construction, MPC 2012, 2012)
Provable security. The goal of provable security is to verify rigorously the security of cryptographic systems. A provable security argument proceeds in three steps: Define a security goal and an adversarial model; Define the cryptographic system and the security assumptions upon which the security of the system hinges; Show by reduction that any attack against the cryptographic system can be used to build an efficient algorithm that breaks a security assumption.